Effects of different proportions of organic substitution for mineral fertilizers on soil methanogenic and methanotrophic communities in paddy fields - Dandan Yuan; Keke Dang; Jing Yin; Han Liu; Tingting Ma; Jia Liu; Xingjia Xiang (PeerJ)
Mineral fertilizers are widely used to improve rice yields, but their overuse has caused severe environmental problems. Replacing mineral fertilizers with organic alternatives might be an effective practice for enhancing agro-ecosystems. This study investigated treatments with varying proportions of organic substitution to determine the optimal approach for increasing soil fertility and rice yield. In addition, the relationship between soil methane emission characteristics and associated microbial communities was studied by microcosm experiments and high-throughput sequencing to assess greenhouse gas emissions. Compared with mineral fertilizers alone, treatment with organic substitution, especially at high proportions, increased soil pH, fertility, and crop yield. Treatment with a medium proportion of organic substitution increased cumulative methane (CH4) emissions by 44.8% relative to mineral fertilization alone, but that with low and high proportions showed similar emissions compared with mineral fertilization alone. Organic substitution treatment significantly increased the gene copy numbers of soil methanogens and methanotrophs, with the highest increases observed under high proportions of organic substitution. The gene copy number of methanogens increased by 4.87 times, and that of methanophiles increased by 13.11 times. Additionally, organic substitution treatment significantly changed their community compositions. High organic substitution was associated with an exceptionally high abundance of methanotrophs. Treatment with a high proportion of organic substitution enhanced the relative abundance of Type I taxa of methanotrophs and increased soil pH to trigger higher pmoA abundance, thus strengthening methane oxidation capacity without additional cumulative CH4 emissions compared with mineral fertilizers alone. Besides, treatment with a high proportion of organic substitution increased crop yield and reduced the amount of mineral fertilizers needed, resulting in less environmental pollution. This study comprehensively evaluated the effects of organic substitution for mineral fertilizers, providing an essential theoretical basis for the sustainable development of agriculture.